Esthetic Reconstruction of Diastema with Adhesive Tooth-Colored Restorations and Hyaluronic Acid Fillers - Supawadee Naorungroj (Case Reports in Dentistry)
Objective. This report presents a comprehensive esthetic treatment with adhesive tooth-colored restorations in a combination with hyaluronic acid (HA) fillers of diastema in an orthodontic patient with relapse. Case Report. A 36-year-old female patient consulted about 1.5–2 mm midline diastema after an orthodontic relapse of replacing missing central incisors with lateral incisors and dark-colored gingival tissue as a result of a metal post and core with porcelain fused to a metal (PFM) crown at the left lateral incisor. Restorative treatments included replacing the PFM with all-ceramic material and placing a ceramic veneer on the right lateral incisor. To close the space, crown forms of both lateral incisors were altered. A direct resin composite was then used to reform right and left canines to a more ideal lateral incisor shape. An HA fillers injection was used to fill the remaining open gingival embrasure. Eighteen months after treatment, the interdental papilla remained stable and the patient was satisfied with the result. Conclusion. Esthetic reconstruction of diastema and open gingival embrasure in this case can be accomplished without orthodontic retreatment. Tooth-colored restorations and HA filler injection appear as a promising modality to address this patient’s esthetic concern.